2014
DOI: 10.4161/mabs.36242
|View full text |Cite
|
Sign up to set email alerts
|

Russell body phenotype is preferentially induced by IgG mAb clones with high intrinsic condensation propensity: Relations between the biosynthetic events in the ER and solution behaviors in vitro

Abstract: The underlying reasons for why some mAb (monoclonal antibody) clones are much more inclined to induce a Russell body (RB) phenotype during immunoglobulin biosynthesis remain elusive. Although RBs are morphologically understood as enlarged globular aggregates of immunoglobulins deposited in the endoplasmic reticulum (ER), little is known about the properties of the RB-inducing mAb clones as secretory cargo and their physical behaviors in the extracellular space. To elucidate how RB-inducing propensities, secret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
24
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 37 publications
12
24
0
Order By: Relevance
“…The biosynthetic steps of such cryoglobulins have also been rarely investigated because of the difficulty in isolating patient‐derived plasma cell clones producing such cryoglobulins. Furthermore, although Russell body and related cellular phenotypes of immunoglobulin‐expressing cells have been known for more than a century, the precise reasons why such phenotypes arise and why different types of cell phenotypes come about remain enigmatic .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The biosynthetic steps of such cryoglobulins have also been rarely investigated because of the difficulty in isolating patient‐derived plasma cell clones producing such cryoglobulins. Furthermore, although Russell body and related cellular phenotypes of immunoglobulin‐expressing cells have been known for more than a century, the precise reasons why such phenotypes arise and why different types of cell phenotypes come about remain enigmatic .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that intracellular phase separation events in the endoplasmic reticulum (ER) contribute to the induction of certain classes of cell‐ular phenotypes in immunoglobulin‐expressing cells . Depending on the intrinsic physicochemical properties of a cargo (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Historically, a number of computational and analytical screening methods have been used to predict aggregation [28][29][30] and high concentration formulation risks. 17,[31][32][33][34][35][36] While these approaches can provide valuable information and help screening of potential lead candidates during discovery and early stage development, they do not necessarily provide insight into the underlying molecular mechanisms involved. With regard to high concentration challenges, the availability of methodologies that can probe native intermolecular interactions at the structural and molecular level can effectively guide corresponding protein engineering and formulation efforts designed to mitigate the development risks.…”
Section: Introductionmentioning
confidence: 99%
“…Similar structures can be found in plasma cells undergoing excessive synthesis of IgGs, especially as a manifestation of physiological abnormalities like multiple myeloma, inflammatory diseases, and autoimmune disorders (Decourt, Galea, Sirac, & Cogné, ; Jiang et al, ). Nevertheless, RBs have also been identified in recombinant IgG producing cell lines such as CHO and HEK293 (Hasegawa et al, ; Hasegawa, Woods, Kinderman, He, & Lim, ; Stoops, Byrd, & Hasegawa, ) as well as during overexpression of bispecific antibody formats in CHO cells (Mathias et al, ). Interestingly, this vesicularized phenotypic appearance of the ER has also been described independently in the context of several different and very diverse conditions including oxidative stress (Hendershot et al, ; Wei et al, ), downregulation of chaperones (Lee, Chu, Iwakoshi, & Glimcher, ; Li et al, ), and parts of the ERAD machinery (Sun et al, ).…”
Section: Discussionmentioning
confidence: 99%